How Children Become Sensitive to the Morphological Structure of the Words That They Read - Deacon, S. H.; Francis, Kathryn A. (Frontiers in Psychology, 2017)
Background. We tested the predictions of models of word reading development as to the effects of repeated exposure on reading of derived words. Aim. Our goal was to examine the impacts of variables that quantify different aspects of this exposure: base frequency, family frequency, and family size. Methods and Samples. In Experiment 1, we asked 75 children in Grades 3 and 5 to read derived words with low surface frequencies (e.g., questionable) that varied in base frequency, family frequency, and family size. In Experiment 2, we asked 41 adults to read the same set of words. Results. In Experiment 1, only base frequency made a contribution that was independent of the other two variables of interest (family size and family frequency) and the control variables (surface frequency, semantic relatedness, and neighbourhood size). In Experiment 2, a similar pattern of results emerged, this time on reading speed. Conclusions. Together, results of these two studies suggest that base frequency has a special role in both children’s and adults’ reading of morphologically complex words. These findings suggest that it plays a specific role in development and maintenance of sensitivity to morphological structure in reading.